Evaluación in vitro del efecto antibacteriano y citotóxico del extracto metanólico de Physalis peruviana (capulí) sobre cepas de Streptococcus mutans (ATCC25175), Streptococcus sanguinis (ATCC 10556) - Huertas Campos, Mariana Cecilia (2015)
Objective: The aim of this study was to evaluate the antibacterial effect of Physalis peruviana on Streptococcus mutans (ATCC 25175) and Streptococcus sanguinis (ATCC 10556). Materials y Methods: The present in vitro experimental study was to determinate the antibacterial effect of the fruit of Physalis Peruviana’s methanolic extract against Streptococcus mutans (ATCC 25175) and Streptococcus sanguinis (ATCC 10556) and Clorhexidine (CHX) as control group, the minimum inhibitory concentration (MIC) and citotoxicity. For the antibacterial assay, 14 wells were prepared from the extract and Clorhexidine 0.12% as a positive control for each bacteria. The method used was agar diffusion test preparing wells with the experimental solutions cultivated in anaerobic conditions for 48 hours at 37ºC, after this time, the growth inhibition was analysed in milimiters. with wells. Results: It was found antibacterial effect of the metanolic extract of the fruit in Streptococcus mutans and Streptococcus sanguinis. In the first group, the inhibicion halo of the extract was 19.15mm ± 1.83 and for Clorhexidine 25.78mm ± 2.27, while for the group of Streptococcus sanguinis, the Physalis Peruviana’s extract had 18.56mm ± 1.59 for inhibicion halos and 22.92mm ± 1.96 for Clorhexidine. On the other hand, the extract’s MIC was 50mg/ml. Finally, the methanolic extract of Physalis peruviana inhibited 50% of viability cells (CC50) at 241.01ug/ml concentration. Conclusions: The methanolic extract of Physalis Peruviana had antibacterial effect against Streptococcus mutans and Streptococcus sanguinis. Besides, this fruit wasn’t citotoxic for Jurkat’s line cell.